2016
DOI: 10.1177/0300985816658100
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial Hepatitis of Tilapia (Oreochromis niloticus L.) is Associated With Orthomyxovirus-Like Virions in Hepatocytes

Abstract: Using transmission electron microscopy (TEM), the presented work expands on the ultrastructural findings of an earlier report on "syncytial hepatitis," a novel disease of tilapia (SHT). Briefly, TEM confirmed the presence of an orthomyxovirus-like virus within the diseased hepatocytes but not within the endothelium. This was supported by observing extracellular and intracellular (mostly intraendosomal), 60-100 nm round virions with a trilaminar capsid containing up to 7 electron-dense aggregates. Other pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 24 publications
7
77
0
2
Order By: Relevance
“…To further examine the developed nested RT-PCR, we applied it to detect TiLV RNA in liver samples preserved in RNAlater reagent, which were taken from South American tilapia showing signs of syncytial hepatitis (11,12), or from healthy controls. This test was performed in a blinded way using the following procedure: the presence or absence of TiLV RNA in the samples was tested by RT-PCR (12) at St. George's University, Grenada.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further examine the developed nested RT-PCR, we applied it to detect TiLV RNA in liver samples preserved in RNAlater reagent, which were taken from South American tilapia showing signs of syncytial hepatitis (11,12), or from healthy controls. This test was performed in a blinded way using the following procedure: the presence or absence of TiLV RNA in the samples was tested by RT-PCR (12) at St. George's University, Grenada.…”
Section: Resultsmentioning
confidence: 99%
“…High mortalities were also observed in naive tilapia exposed to an isolate of TiLV (10). Tilapia mortality, suspected of having a viral etiology, has also been described in Ecuador (11,12). Although variations in pathological presentation have been described (where lesions were focused in the central nervous system or in the liver, in Israel or Ecuador, respectively), sequencing the whole genome of TiLV revealed that tilapia in the two countries were infected with almost identical viruses (4).…”
mentioning
confidence: 99%
“…Sixty‐seven asymptomatic fish were also obtained from ponds without excess mortality. Specific RT–PCR assays were performed accordingly (del‐Pozo et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Presence of SHT was defined as excess mortality between 28,000 and 40,000 deaths per 100,000 fish per production cycle, weak to strong positive band signals on RT–PCR for the orthomyxo‐like virus correlating with low (asymptomatic fish) to high viral loads (classical clinical signs), necrotizing hepatitis and syncytia giant cell formation (Bacharach et al., ; Ferguson et al., ; del‐Pozo et al., ). A modified Poisson regression model was constructed and used to determine the production‐level risk factors for the presence of SHT with the dependent variable, excess mortality being dichotomously categorized as a present or absent variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation